A long-term analysis of oxidant (OX = O3 + NO2) and its local and regional levels in Tehran, Iran, a high NOx-saturated condition - Ahmad Taheri; Babak Khorsandi; Mohammad Reza Alavi Moghaddam (Scientific Reports)
Abstract Oxidant (OX), the sum of ozone (O3) and nitrogen dioxide (NO2), is used to determine nitrogen oxides (NOx)-independent regional contribution and NOx-dependent local contribution. This study investigates OX trends and its local and regional levels in Tehran, Iran using the data from 21 monitoring stations from 2012 to 2022 and satellite remote sensing data (TROPOMI) for 2022. The spatiotemporal trends of O3, NO2, and OX are first examined using ground-based and remote sensing data, and then the polar plots are employed to identify the dominant directions of OX transport and its sources. Subsequently, the local and regional contributions of OX were determined using OX-NOx relationship. The findings indicated that the OX trend is primarily affected by O3 fluctuations during the warmer months, whereas NO2 variations have a stronger correlation with OX during the remaining months. The emissions from the central zone of the city were mostly caused by the transportation fleet. The emissions from industries in the south also have a significant effect on the city’s OX concentration. Moreover, the local contribution of OX, reaching a maximum value of 0.15 ppb/ppb NOx (for both monthly and yearly analysis), contributes to the elevation of OX levels during nighttime. In contrast, the OX local contribution at daylight hours is mostly negative, with minimum values of − 0.15 ppb/ppb NOx for July and − 0.07 ppb/ppb NOx for 2012, indicating a decrease in the OX concentration with an increase in the local NOx emission. Furthermore, the OX levels, especially for daylight hours, is mostly related to its regional contribution with maximum of 100 ppb in July and 95 ppb in 2017, suggesting the necessity of considering regional emissions in developing mitigation scenarios. Lastly, our results indicate that the transportation fleet plays an undeniable role in contributing to the local emissions in Tehran.